Biometrics: a look at face recognition / Loimih Ramidi - Ramidi, Loimih (Faculty of Information Technology and Quantitative Sciences, 2005)
Biometrics are automated methods of recognizing a person based on a physiological or behavioral characteristic. Biometric technologies are becoming the foundation of an extensive array of highly secure identification and personal verification solutions. Face authentication is a fairly young technology compared to other biometrics. Research in this field has been going on for decades, but it has been in the last 10 to 15 years that the greatest advances have taken place. The analysis process over the years has moved away from using the simple geometry of key facial points to the use of more complex mathematical techniques.